Efficacy of Autologous Injectable Platelet Rich Fibrin in Facial Atrophic Acne Scars in Combination with Microneedling: A Randomized Clinical Trial - Katyayani Pandey; Sudha Agrawal; Prajwal Pandey (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Several modalities for treating acne scars exist. The combination of microneedling and injectable platelet-rich fibrin (i-PRF) is a synergistic approach.